Octa-substituted metallophthalocyanines bearing (2,3-dihydrobenzo-1,4-benzodioxin-2-yl)methoxy and chloro groups: Synthesis, characterization and photophysicochemical studies - Gorduk, Semih (WORLD SCIENTIFIC PUBL CO PTE LTD, 2020)
In this study, the synthesis and characterization of novel 4-chloro-5-((2,3-dihydrobenzo-1,4-benzodioxin-2-yl-methoxy)phthalonitrile (1) and its peripherally octa-substituted Zn(II) (Pc-Zn), In(III) (Pc-InCI) and Mg(II) (Pc-Mg) phthalocyanine (Pc) derivatives are reported for the first time. FTIR, elemental analysis, UV-vis, NMR and MS techniques were used for characterization studies of the compounds. Aggregation properties of the compounds were evaluated in DMF, DMSO and 'IMF solvents in different concentrations, and the compounds did not tend to aggregate in these solvents. In addition, photophysicochemical properties such as fluorescence, photodegradation and singlet oxygen quantum yield of the compounds were examined in DMSO, DMF and THF solvents to show the potential use of these novel compounds as photosensitizers for photodynamic therapy (PDT). The effects of zinc, indium and magnesium metals, octa substitutions in peripheral positions and different types of solvents on photophysicochemical properties were investigated. The singlet oxygen quantum yield values of compounds ranged from 0.27 to 0.77 in different solvents. As a result of the photophysicochemical properties, these compounds can be considered as potential candidates for PDT, applications.
Keywords: phthalocyanine; benzodioxan; singlet oxygen; photophysicochemical; chloro; PHOTODYNAMIC ANTIMICROBIAL CHEMOTHERAPY; PHOTOCHEMICAL PROPERTIES; ZINC PHTHALOCYANINE; TETRA-TRIETHYLENEOXYSULFONYL; SOLUBLE PHTHALOCYANINES; CARBOXYLIC-ACID; DERIVATIVES; PHOTOSENSITIZERS; THERAPY; MECHANISMS; Chemistry